Two New Lightweight Cryptographic Hash Functions Based on Saturnin and Beetle for the Internet of Things - Windarta, Susila; Suryadi, Suryadi; Ramli, Kalamullah; Lestari, Andriani Adi; Wildan, Wildan; Pranggono, Bernardi; Wardhani, Rini Wisnu (IEEE access, 2023)
With the enormous growth in Internet of Things (IoT) applications, the volume of data shared among IoT devices is vastly increasing. Extensive IoT device connectivity and substantial data transmission have made information integrity susceptible to various assaults. Therefore, hash functions are required to ensure data integrity in IoT networks. IoT systems are constrained by their complexity, necessitating the consumption of minimal computational power. As a result, lightweight hash functions have been selected as the solution for the IoT data integrity issue. We present two lightweight hash functions, Alit-Hash and Tjuilik-Hash, based on the Saturnin block cipher and the Beetle mode of operation. In particular, we created Tjuilik-Hash by modifying the Saturnin block cipher. The strength of the proposed hash functions is evaluated through security analysis and performance testing. Alit-Hash and Tjuilik-Hash both show reasonably good resistance to differential and linear cryptanalysis. Hardware implementations on a cost-effective and low-power microcontroller board (ATmega2560) demonstrate an average execution time of 0.746 microseconds for the Tjuilik-Hash algorithm. Performance evaluations on a 64-bit personal computer indicate that the Alit-Hash and Tjuilik-Hash implementations exhibit comparable speed and throughput to seven other evaluated hash functions. Simulation experiments employing Contiki-NG and the Cooja simulator confirm the good performance of these two hash functions relative to Photon-Beetle-Hash, Photon, and Spongent across five metrics. The hash functions pass seven cryptographic randomness tests and pass all tests in the National Institute of Standards and Technology (NIST) Statistical Test Suite (STS). Therefore, the implementation of both proposed hash functions should be considered, as they are both cost-effective and provide an adequate level of security, which is essential for IoT devices with limited resources.